(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdNeS hgh Mb eGdj aQVg Gddg eGdc Gdedc Ydi YHGOg aj eGd eNUhU Ch dHfj gGTe GdPjf ge QDSGFge hShGSge hCgd GdaVd hGdEMSGf Ydjge YhV CcQGeg EjGges
(3BNQgG (B:s
(3BNQgG(B: (3dCf eKdG aj edc GdbGFe jJhba Ydi bHhd hfMhg de jcf dg GdbHhd jOd Ydi YOe Yehe hdGjJg Yf GdZGFHjf aj CeKGd Pdc (B.. (3NGUI aj MaX (B.. (3eG jLH Yfge(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis